Consent forms: the participation of children in research - Fialho, Flavia Andrade Nunes; Dias, Ieda Maria Ávila Vargas; Rego, Marisa Palacios da Cunha Melo de Almeida (Revista Bioética, 2022)
The Resolution 466/2012 of the National Council of Health establishes the term of assent as compulsory for research carried out with children. However, the resolution presents the definition of assent without specifying the terms necessary for the document. This gap makes current and pertinent the approach of this topic by this study, which aims to discuss the participation of children in research. The results present a theoretical framework from which we can reflect on the ethics of Research with children, considering their vulnerability, which can lead to irreparable situations. We conclude that the theme must remain in the academic and professional debates since, on top of being a dynamic reality, this population segment has many specificities.